Beyond the core : reflections on regionality in prehistory - Jones, Andy M.; Kirkham, Graeme (Oxbow Books, 2011)
This volume explores the idea of regionally-based archaeologies across the British Isles which are not necessarily defined by modern political boundaries or through comparisons with regions such as Wessex and Orkney. In the past these intensively studied areas have often been assumed to represent the 'typical' - other areas with apparently different narratives have generally been labelled 'peripheral' and their diversity and distinctiveness overlooked. Assumptions about these core-based models have been challenged, especially by archaeologists in Ireland and Scotland and to some extent Wales.